The validity of nominee agreements on the ownership of shares from a business law and human rights perspective - Mustika, I Komang Sanju Bayu (The International Journal of Politics and Sociology Research, 2025)
This study analyzes the validity of nominee agreements in share ownership under Indonesian investment law through the perspective of human rights theory. Using a normative juridical method, the research examines how such agreements, often used to conceal foreign ownership, relate to national legal norms and human rights principles, including economic rights, equality before the law, and the right to national self-determination. The study draws on primary legal sources such as the Investment Law (Law No. 25 of 2007), the Company Law (Law No. 40 of 2007), and constitutional provisions under the 1945 Constitution, along with relevant international human rights instruments. The findings demonstrate that nominee agreements violate Article 33 of the Investment Law and contradict Indonesia’s constitutional and human rights commitments. These agreements not only obscure ownership transparency but also undermine economic justice and the collective rights of Indonesian citizens to control national resources. The research concludes that maintaining the prohibition of nominee arrangements is essential to preserving legal certainty, national sovereignty, and the ethical integrity of foreign investment practices. The alignment of investment law with human rights principles strengthens Indonesia’s commitment to fair, transparent, and sustainable economic governance.